First report of group A rotavirus and bovine coronavirus associated with neonatal calf diarrhea in the northwest of Argentina - Bertoni, Emiliano Agustín; Aduriz Guerrero, Matías; Bok, Marina; Vega, Celina Guadalupe; Saif, Linda J.; Aguirre, Daniel Hector; Cimino, Rubén Oscar; Miño, Samuel; Parreño, Gladys Viviana (Springer, 2020)
Group A rotavirus (RVA) and bovine coronavirus (BCoV) are the two main viral enteropathogens associated with neonatal calf diarrhea. The aim of the present survey was to investigate the epidemiology and the role of RVA and BCoV in the presentation of dairy and beef calf diarrhea in Lerma Valley of Salta province, within the Northwest region of Argentina. Stool samples of calves with or without diarrhea younger than 2 months of age were collected from 19 dairy farms and 20 beef farms between the years 2014 and 2016. Stool samples were screened for RVA and BCoV detection by ELISA. Heminested multiplex RT-PCR was used for RVA typing and RT-PCR to confirm BCoV. Positive samples were submitted to sequencing analysis. Bovine RVA and BCoV were circulating in 63% (12/19) and 10.52% (2/19) of the dairy farms, respectively, where 9.5% (46/484) of the calves were positives to RVA and 0.4% (2/484) to BCoV. In beef herds, RVA was detected in 40% (8/20) of the farms and in 6.75% (21/311) of the calves, without positives cases of BCoV. Molecular analysis showed that in dairy farms, G6P[11] and G10P[11] were the prevalent RVA strains, while in beef farms, G10P[11] was the prevalent. The main finding was the detection for the first time of a G15P[11] causing diarrhea in beef calves of Argentina that represents a new alert to be consider for future vaccine updates. Analysis of detected BCoV showed that it is related to the other circulating strains of Argentina.